Omics for aquatic ecotoxicology: Control of extraneous variability to enhance the analysis of environmental effects. (22nd June 2015) - Simmons, Denina B.D.; Benskin, Jonathan P.; Cosgrove, John R.; Duncker, Bernard P.; Ekman, Drew R.; Martyniuk, Christopher J.; Sherry, James P.
Abstract: There are multiple sources of biological and technical variation in a typical ecotoxicology study that may not be revealed by traditional endpoints but that become apparent in an omics dataset. As researchers increasingly apply omics technologies to environmental studies, it will be necessary to understand and control the main source(s) of variability to facilitate meaningful interpretation of such data. For instance, can variability in omics studies be addressed by changing the approach to study design and data analysis? Are there statistical methods that can be employed to correctly interpret omics data and make use of unattributed, inherent variability? The present study presents a review of experimental design and statistical considerations applicable to the use of omics methods in systems toxicology studies. In addition to highlighting potential sources that contribute to experimental variability, this review suggests strategies with which to reduce and/or control such variability so as to improve reliability, reproducibility, and ultimately the application of omics data for systems toxicology. Environ Toxicol Chem 2015;34:1693–1704. © 2015 SETAC